Intensive Methods For Developing Design Skills In The Professional Activities Of Engineering Students (Journal of Pedagogical Inventions and Practices, 2025)
The article provides a detailed and comprehensive analysis of the role of engineering and computer graphics in the professional training system of engineering students, as well as the mechanisms for developing graphic design skills. Nowadays, the advancement of engineering demands extensive application of newgeneration technical equipment, devices, and modern digital technologies. Accordingly, the theoretical and practical aspects of forming 2D and 3D design skills related to industry-specific equipment, products, and parts among engineering students are thoroughly examined in this research. The author systematically analyses existing challenges in the educational process, including students’ difficulties in applying theoretical knowledge in practice, insufficiently developed software application skills, and ineffective use of pedagogical methods during teaching. To address these issues, the author proposes the implementation of modern pedagogical technologies, engaging students in small-group project-based and practical assignments, and systematically organizing practical classes using specialized computer graphics software (such as AutoCAD, SolidWorks, and Compass 3D). Furthermore, the scientific and practical importance of extensively employing interactive methods that enhance students' independent work and critical thinking skills—such as Project-Based Learning, trainings, and intensive practical sessions—is substantiated. Additionally, the article outlines specific criteria developed to evaluate the effectiveness of the proposed methods and approaches, demonstrating their potential to improve students’ professional competencies, design speed, and quality. As a result, it is emphasized that these approaches will significantly develop students' innovative, creative, and analytical thinking abilities, consequently broadening opportunities for preparing competitive engineering professionals in alignment with the requirements of the labor market